Treinamento muscular inspiratório para asma: revisão sistemática com metanálise - Silva, Ivanizia Soares da (2012)
In asthmatic, the lung hyperinflation leaves the inspiratory muscle at a suboptimal position in length-tension relationship, reducing the capacity of to generate tension. The increase in transversal section area of the inspiratory muscles could reverse or delay the deterioration of inspiratory muscle function. Objective: To evaluate the evidence for the efficacy of inspiratory muscle training (IMT) with an external resistive device in patients with asthma. Methods: A systematic review with meta-analysis was carried out. The sources researched were the Cochrane Airways Group Specialised Register of trials, Cochrane Central Register of Controlled Trials (The Cochrane Library Issue 11 of 12, 2012), MEDLINE, EMBASE, PsycINFO, CINAHL, AMED, ClinicalTrials.gov and reference lists of articles. All databases were searched from their inception up to November 2012 and there was no restriction on the language of publication. Randomised controlled trials that involved the use of an external inspiratory muscle training device versus a control (sham or no inspiratory training device) were considered for inclusion. Two reviewers independently selected articles for inclusion, evaluated risk of bias in studies and extracted data. Results: A total of five studies involving 113 asthmatic patients were included. Three clinical trials were produced by the same group. The included studies showed a significant increase in maximal inspiratory pressure (MD 13.34 cmH2O, 95% CI 4.70 to 21.98), although the confidence intervals were wide. There was no statistically significant difference between the IMT group and the control group for maximal expiratory pressure, peak expiratory flow rate, forced expiratory volume in one second, forced vital capacity, sensation of dyspnea and use of beta2-agonist. There were no studies describing exacerbation events that required a course of oral and inhaled corticosteroids or emergency department visits, inspiratory muscle endurance, hospital admissions and days of work or school. Conclusions: There is no conclusive evidence in this review to support or refute inspiratory muscle training for asthma, once the evidence was limited by the small number of studies included, number of participants in them together with the risk of bias. More well conducted randomized controlled trials are needed, such trials should investigate respiratory muscle strength, exacerbation rate, lung function, symptoms, hospital admissions, use of medications and days off work or school. IMT should also be assessed in the context of more severe asthma